2007
DOI: 10.1111/j.1939-1676.2007.tb03019.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Low‐Dose Oral Chemotherapy for Adjuvant Therapy of Splenic Hemangiosarcoma in Dogs

Abstract: Continuous orally administered LDC may be an effective alternative to conventional high-dose chemotherapy for adjuvant therapy of dogs with HSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 33 publications
(38 reference statements)
3
132
1
4
Order By: Relevance
“…This consisted of a 3-hour F14512 i.v. infusion once daily for 3 consecutive days, repeated every 2 weeks (days 1-3, days 15-17, and days [22][23][24]. The first dose level of 0.05 mg/kg and the schedule of administration were chosen following previous preclinical studies performed in beagle dogs and to be consistent with ongoing and future clinical trials in humans.…”
Section: Treatment Schedulementioning
confidence: 99%
See 1 more Smart Citation
“…This consisted of a 3-hour F14512 i.v. infusion once daily for 3 consecutive days, repeated every 2 weeks (days 1-3, days 15-17, and days [22][23][24]. The first dose level of 0.05 mg/kg and the schedule of administration were chosen following previous preclinical studies performed in beagle dogs and to be consistent with ongoing and future clinical trials in humans.…”
Section: Treatment Schedulementioning
confidence: 99%
“…Etoposide has been extensively studied in dogs for pharmacokinetics (PK) and toxicologic purposes (20,21), but little data are available concerning its potential antitumor efficacy in pet dogs (22,23). A retrospective study on 13 dogs with relapsing lymphoma treated with etoposide (24) showed that etoposide had a minimal therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…8,11,13,14 Chemotherapy in the adjuvant setting has been evaluated in various clinical studies and has shown promise in prolonging life after surgical resection of the primary HSA lesion. [15][16][17][18][19] Most of those studies included dogs with different clinical stages of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The fi rst full paper was not published for another 6 years [ 50 ]. It compared the outcome of nine dogs with splenic hemangiosarcoma treated with a traditional doxorubicin protocol dose-intense single-agent chemotherapy and nine dogs with the same disease treated with metronomic chemotherapy.…”
Section: Metronomic Chemotherapy In Dogsmentioning
confidence: 98%